A Quasi-Conservative Discontinuous Finite Element Method for Nuclear Reactor Point Kinetics Model - García, C.R.; Domínguez, D.S.; Barros, R.C. (Trends in Computational and Applied Mathematics, 2003)
The point reactor kinetics model is an initial value problem characterized by a system of ordinary differential equations that describe the time dependence of the neutron population within a nuclear reactor and core and the decay of the delayed neutron precursors.